Charles Dudley Warner papers - Warner, Charles Dudley, 1829-1900.
Chiefly ALsS from Warner to James R. Osgood pertaining to Warner's writing and publishing. Also includes a manuscript page from The Gilded Age: A Tale of Today (1874) and an account of Abraham Lincoln's inauguration in March 1865.
Author and newspaper editor from Hartford, Conn.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Inauguration, 1865.; Osgood, James R. -- 1836-1892 -- Correspondence; American literature; American newspapers -- Connecticut -- Hartford; Authors; Editors